Chitosan-Dextran-Glycerol Hydrogels Loaded with Iron Oxide Nanoparticles for Wound Dressing Applications - Cristina Chircov; Iuliana Teodora Bejenaru; Adrian Ionuț Nicoară; Alexandra Cătălina Bîrcă; Ovidiu Cristian Oprea; Bianca Tihăuan (MDPI AG, 2022)
Natural polymers have shown tremendous potential towards the development of hydrogels with tissue regeneration properties. Among them, chitosan and dextran are polysaccharides widely applied in the wound dressing area owing to their mucoadhesiveness, biodegradability, hemostatic potential, and intrinsic antibacterial activity, while glycerol is a well-known biocompatible solvent extensively used in the manufacture of cosmetic, pharmaceutical, medical, and personal care products. In order to enhance the properties of natural polymer-based hydrogels, the focus has currently shifted towards the addition of nanomaterials with antibacterial and regenerative potential, i.e., iron oxide nanoparticles. Thus, the aim of the present study was to develop a series of chitosan-dextran-glycerol hydrogels loaded with iron oxide nanoparticles, either readily added or formed in situ. The physicochemical properties of the so obtained hydrogels demonstrated an improved dispersibility of the in situ formed magnetite nanoparticles, which further decreases the porosity and swelling ratio of the hydrogels but increases the antimicrobial properties. Additionally, the presence of glycerol enhances the cell viability but reduces the antimicrobial potential. In this context, the results proved promising biological and antimicrobial properties, thus confirming their potential as biomaterials for wound healing and regeneration.